2017
DOI: 10.1016/j.quageo.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Holocene-Neogene volcanism in northeastern Australia: Chronology and eruption history

Abstract: Quaternary and late Neogene volcanism is widespread in northeastern Australia, producing at least 397 eruptions covering more than 20,000 km 2 , including at least 20 flows over 50 km long. Despite this abundance of young volcanism, before this study numerous eruptions had tentative ages or were undated, and the area requires a comprehensive evaluation of eruption patterns through time. To help address these issues we applied multi-collector ARGUS-V 40 Ar/ 39 Ar geochronology to determine the age of four of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“… Note . Age ranges compiled from different studies (Cohen et al., 2008, 2013, 2017; Crossingham et al., 2017; 2018; Gibson, 2007; Gray & McDougall, 2009; Jones, 2018; Jones et al., 2017; Matchan & Phillips, 2014; Sutherland et al., 2012, 2014; Vasconcelos et al., 2008). Bracketed letters act as key for provinces labeled in Figure 1.…”
Section: Upper Mantle Structurementioning
confidence: 99%
See 1 more Smart Citation
“… Note . Age ranges compiled from different studies (Cohen et al., 2008, 2013, 2017; Crossingham et al., 2017; 2018; Gibson, 2007; Gray & McDougall, 2009; Jones, 2018; Jones et al., 2017; Matchan & Phillips, 2014; Sutherland et al., 2012, 2014; Vasconcelos et al., 2008). Bracketed letters act as key for provinces labeled in Figure 1.…”
Section: Upper Mantle Structurementioning
confidence: 99%
“… Topographic map of northern and central Queensland showing chronology of Cenozoic volcanic provinces (Cohen et al., 2017; Coventry et al., 1985; Gibson, 2007; Griffin & McDougall, 1975; Johnson, 1989; Jones et al., 2020; Stephenson & Griffith, 1976; Stephenson et al., 1998; Whitehead et al., 2007; Wyatt & Webb, 1970). Black polygons = surface expression of volcanism; circles/triangles = loci of age‐independent/‐progressive whole‐rock geochemical analyses; red/white fill = newly acquired/legacy data (Jones et al., 2020; O'Reilly & Zhang, 1995; Stephenson et al., 2000; Zhang et al., 2001).…”
Section: Upper Mantle Structurementioning
confidence: 99%
“…Hamacher and Norris (2016) related known cosmic impacts and meteorite falls to Australian Aboriginal stories. Scientific investigations have confirmed Traditional Knowledge of Quaternary volcanism by the Gugu Badhun people in Queensland, Australia (Cohen et al 2017). Landscape features which feature in Indigenous stories have been identified beneath the sea at multiple locations around Australia, indicating that the stories pre-date the most recent period of post-glacial sea-level rise 7000 years ago, (Nunn and Reid 2016).…”
Section: Introductionmentioning
confidence: 82%
“…Some recent studies – mostly in disciplines other than archaeology – have suggested that Indigenous oral traditions preserve deep-time knowledge of volcanic activity and climate change (see, e.g. Cohen et al., 2017; Nunn, 2018; papers in Picardi and Masse, 2007). Nunn and Reid (2016) have suggested that Australian Aboriginal oral traditions describe sea level rise events around Australia which occurred in the period 7,250 to 13,070 years cal.…”
Section: Some Implications Of Indigenous Archaeologiesmentioning
confidence: 99%